Performance Test of High-temperature Immersion Pump for In-reactor Purification of Integrated Fast Reactor - LI Xu1, GENG Xiao1, YAO Zewen1, , YU Chunli1, WU Peng2, YU Genfang2 (Yuanzineng kexue jishu)
In the integrated fast reactor project of the China Institute of Atomic Energy, in order to keep the primary circuit sodium within the reactor and prevent radioactive sodium leakage, an in-reactor cold trap is used to purify the impurities in the sodium, enabling the purification of the primary circuit sodium inside the reactor vessel. Considering that it is impossible to use the pressure difference to feed sodium into the equipment, the external electromagnetic pump can no longer meet the usage requirements. The electromagnetic pump needs to be installed in the sodium pool, and the pump trench can be filled with sodium when the equipment is put in. Therefore, to meet the purification requirements of the in-reactor cold trap, it is necessary to develop a new in-reactor sodium pumping device. The immersion pump needs to be installed at the bottom of the cold trap, sucking sodium from the sodium pool and injecting it into the inner cylinder of the in-reactor cold trap through the top outlet, providing stable and adjustable power for the cyclic purification of sodium in the cold trap. A high-temperature immersion pump suitable for the in-reactor cold trap was designed in this paper. The immersion pump sucks sodium from the sodium pool and injects it into the inner cylinder of the in-reactor cold trap through the top outlet, providing stable and adjustable power for the cyclic purification of sodium in the cold trap. For the prototype of the high-temperature immersion pump, performance tests were carried out in a simulated in-reactor sodium environment. The flow-head curve, flow-efficiency curve, flow-power curve of the immersion pump under different power conditions, as well as the test values of the temperatures of key components were obtained, and the test results were analyzed and compared with the simulation calculation results. The results show that the developed prototype of the immersion pump can meet the engineering requirements of a flow rate of 8 m3/h and a head of 0.2 MPa under the high-temperature (360 ℃) sodium medium environment and rated operating conditions. At the same time, the actual temperature of the winding coil is lower than the safe operating temperature (450 ℃), meeting the design requirements. The above results provide support for further in-reactor purification services.